Otimização da capacidade de arranjos MIMO usando algoritmo genético - Binelo, Manuel Osório (2013)
BINELO, M. O. MIMO array capacity optimization using a genetic algorithm. 2013. 78 f. Tese (Doutorado em Engenharia de Teleinformática) - Centro de Tecnologia, Universidade Federal do Ceará, Fortaleza, 2013. === Submitted by Marlene Sousa (mmarlene@ufc.br) on 2013-06-17T14:39:41Z No. of bitstreams: 1 2013_tese_mobinelo.pdf: 14736133 bytes, checksum: 797a64b277045135e858d52477282d64 (MD5) === Approved for entry into archive by Marlene Sousa(mmarlene@ufc.br) on 2013-06-17T16:46:09Z (GMT) No. of bitstreams: 1 2013_tese_mobinelo.pdf: 14736133 bytes, checksum: 797a64b277045135e858d52477282d64 (MD5) === Made available in DSpace on 2013-06-17T16:46:09Z (GMT). No. of bitstreams: 1 2013_tese_mobinelo.pdf: 14736133 bytes, checksum: 797a64b277045135e858d52477282d64 (MD5) Previous issue date: 2013-01 === One challenging task in multiple input multiple output (MIMO) systems design is to accommodate the multiple antennas in the mobile device without compromising the system capacity, due to spatial and electrical constraints. In this work, an experimental MIMO wireless channel characterization in an outdoor environment is performed in order to study the different factors that affect MIMO capacity. The data acquired during wideband channel measurement campaigns made in Stockholm, Sweden, were used in order to predict the impact of direction of arrival (DOA) distribution and polarization diversity on the channel capacity, choosing speciﬁc measurement routes and locations as well as different MIMO antenna array conﬁgurations. This thesis proposes a genetic algorithm (GA) to obtain the position and orientation of each MIMO array antenna that maximizes the ergodic capacity for a given propagation scenario. The simulations of the GA use the characterized experimental channel model, as a case of study, in order to evaluate the impact of different characteristics of the propagation environment in the capacity. Based on an interface between the antenna model and the propagation channel model, the ergodic capacity is considered as the objective function of the MIMO array optimization. Simulation results corroborate the importance of polarization and antenna pattern diversities for MIMO in small terminals. The results also show that the electromagnetic coupling effect can be exploited by the optimizer in order to decrease signal correlation and increase MIMO capacity. A comparison among uniform linear array (ULA), uniform circular array (UCA) and the GA-optimized array is also carried out, showing that the topology given by the optimizer is superior to that of the standard ULA and UCA arrays for the considered propagation channel. This work also presents a method for optimizing the capacity of MIMO antenna array systems with antenna selection, evolving the antenna array best suited for antenna selection in a given scenario. As a result of the proposed GA optimizer, different array conﬁgurations were obtained for cases with and without antenna selection, showing that true polarization diversity (TPD) schemes are particularly suited for antenna selection systems. === Uma questão bastante complicada no projeto de sistemas MIMO é acomodar as múltiplas antenas no dispositivo móvel sem comprometer a capacidade do sistema, devido a restrições elétricas e de espaço. Neste trabalho é desenvolvida a caracterização de um canal MIMO sem fio em ambiente externo para o estudo dos diferentes fatores que afetam a capacidade de comunicação. Os dados adquiridos em campanhas de medição feitas em Estocolmo foram utilizados para modelar o impacto da distribuição de DOA e da diversidade de polarização na capacidade do canal, escolhendo rotas específicas de medida e diferentes configurações de arranjos de antena. Essa tese propõe um algoritmo genético para obter a posição e orientação de cada antena do arranjo MIMO que maximizem a capacidade ergótica para um dado cenário de propagação. Baseando-se em uma interface entre o modelo de antena e o modelo de propagação do canal, a capacidade ergódica é usada como função objetivo da otimização do arranjo MIMO. Os resultados das simulação indicam a importância das diversidades de polarização e de padrão de antena para sistemas MIMO em terminais de pequeno porte. Os resultados também mostram que o efeito do acoplamento eletromagnético pode ser explorado pelo otimizador para diminuir a correlação do sinal aumentando assim a capacidade MIMO. Também é feita uma comparação entre arranjo linear uniforme(ULA), arranjo circular uniforme(UCA) e um arranjo otimizado pelo algoritmo genético, mostrando que a topologia resultante do algoritmo genético é superior tanto a ao arranjo ULA quanto ao arranjo UCA, para o canal de propagação considerado. Este trabalho também apresenta um método para otimização da capacidade de sistemas MIMO com seleção de antena, evoluindo um arranjo de antenas melhor adaptado para a seleção de antenas em um dado cenário de propagação. Como resultado do método proposto, diferentes configurações de arranjos foram obtidas para o caso com e sem seleção de antenas, mostrando que sistemas de diversidade de polarização(TPD) são particularmente adequados para sistemas com seleção de antena.